2008
DOI: 10.1111/j.1464-410x.2008.07513.x
|View full text |Cite
|
Sign up to set email alerts
|

Is robotically assisted laparoscopic radical prostatectomy less invasive than retropubic radical prostatectomy? Results from a prospective, unrandomized, comparative study

Abstract: during surgery (T1), at the end of anaesthesia (T2), and 12 (T3) and 24 h after surgery (T4), and assayed for interleukin(IL)-6 and IL-1 α , C-reactive protein (CRP), and lactate. The Mann-Whitney U -, Student's t-and Friedman tests were used to compare continuous variables, and the Pearson chi-square and Fisher test for categorical variables, with a two-sided P < 0.05 considered to indicate significance. RESULTSIn all, 35 and 26 patients were assessed for RALP and RRP, respectively; the median (interquartile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 24 publications
4
57
1
3
Order By: Relevance
“…In a more recent comparison from the same institution, Kordan et al reported a median EBL of 450 ml in the ORP group compared to 100 ml in the RALP group ( p < 0.001)[24]. Multiple other single-institution series have shown lower EBL in patients treated with RALP than in those treated with ORP[19,21,25,26,27,28]. To our knowledge, no study has demonstrated lower EBL in patients treated with ORP compared to RALP.…”
Section: Comparison and Discussion Of Orp And Ralpmentioning
confidence: 99%
“…In a more recent comparison from the same institution, Kordan et al reported a median EBL of 450 ml in the ORP group compared to 100 ml in the RALP group ( p < 0.001)[24]. Multiple other single-institution series have shown lower EBL in patients treated with RALP than in those treated with ORP[19,21,25,26,27,28]. To our knowledge, no study has demonstrated lower EBL in patients treated with ORP compared to RALP.…”
Section: Comparison and Discussion Of Orp And Ralpmentioning
confidence: 99%
“…The weighted mean operative time (205 min) was longer in those patients who were undergoing LRP compared with the other two approaches. Similarly, the systematic review conducted recently by Ficarra and colleagues 13 suggested that RARP is more time consuming than RRP only in the earlier phase of the learning curve 71 but that such differences disappeared with increased surgical experience. The same meta-analysis also showed that the operative time is significantly longer in those patients who are undergoing LRP compared with RRP.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
“…102 Eight reports 107,111,120,126,139,141,143,147 did not report specific baseline clinical stage, simply reporting their inclusion criterion as '≤ cT1-T2' , and one 109 did not report clinical stage by procedure. The baseline clinical tumour staging was similar between the laparoscopic and robotic radical prostatectomy patients with 68% and 69%, respectively, categorised as T1.…”
Section: Characteristics Of Patientsmentioning
confidence: 99%
“…91,95,96 Of the non-randomised comparative studies comparing robotic, laparoscopic and open radical prostatectomy, two primary studies 99,100 and one secondary report 102 were set in the USA and one study was set in France. 101 Of the nonrandomised comparative studies comparing robotic and open radical prostatectomy, 10 primary studies 103,[108][109][110][111][112][115][116][117][118] and two secondary reports 119,120 were set in the USA, one study was set in Australia, 105 three primary studies 106,107,114 were set in Italy, one study was set in Sweden 104 and one was set in Taiwan, Province of China. 113 Of the non-randomised comparative studies comparing laparoscopic and open radical prostatectomy, seven primary studies [124][125][126]128,142,145,146 and one secondary report 147 were set in the USA, three primary studies 127,131,137 were set in Germany, three primary studies 135,136,144 were set in Japan, three primary studies 123,129,134 were set in Italy, two primary studies 122,140 were set in France and one study each was set in Austria, 139 Brazil,…”
Section: Number and Type Of Included Studiesmentioning
confidence: 99%